Diagnosis of unusual mandibular split fracture with cone-beam computed tomography - Nilüfer Ersan; Mehmet Ilgüy (Wolters Kluwer Medknow Publications, 2015)
Mandibular fractures are relatively easy to diagnose in comparison with other craniofacial fractures. This report presents a trauma patient with an unusual split fracture in the mandibular corpus, which was missed on the panoramic radiograph; however, could be visualized with cone-beam computed tomography (CBCT). Panoramic radiograph may be misleading for accurate diagnosis of mandibular corpus fractures. We suggest that CBCT is crucial and should be mandatory for all suspected mandibular fractures in maxillofacial trauma patients.